2023
DOI: 10.3390/ijerph20032584
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Characteristics and Causes of Night Tourism Accidents in China Based on SNA and QAP Methods

Abstract: The key purpose of this paper is to address an inherent gap in the literature on safety issues in the development of night tourism. This research takes a novel methodological approach, by using 8787 cases of tourism safety accidents in typical night tourism cities in China, and applying social network analysis (SNA) and quadratic assignment procedure (QAP) regression analysis to explore the multidimensional structural characteristics and risk-causing factors of night tourism accidents. Key findings include: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The variable matrix in Equation ( 9) is transformed into an n × (n − 1)-dimensional column vector, that is, a long vector, and then OLS estimation is performed on the long vector to obtain the regression coefficient set Γ(Y, XZ) and goodness of fit R 2 . As mentioned above, due to the autocorrelation problem of relational data, the standard error obtained using the OLS estimation method is wrong [77], and the significance of traditional statistical test methods (such as t-test and F-test) will no longer be reliable. The second step is random permutation and a statistical test.…”
Section: Qap Methodsmentioning
confidence: 99%
“…The variable matrix in Equation ( 9) is transformed into an n × (n − 1)-dimensional column vector, that is, a long vector, and then OLS estimation is performed on the long vector to obtain the regression coefficient set Γ(Y, XZ) and goodness of fit R 2 . As mentioned above, due to the autocorrelation problem of relational data, the standard error obtained using the OLS estimation method is wrong [77], and the significance of traditional statistical test methods (such as t-test and F-test) will no longer be reliable. The second step is random permutation and a statistical test.…”
Section: Qap Methodsmentioning
confidence: 99%
“…Burch has shown that the reward of security is more significant than any possible reward due to the high cost of uncertainty (Burch, 2009). The study's results by Huang et al (2023) show that safety plays a vital role in tourism development, especially the safety of tourism at night, but the safety issue of night tourism receives little attention.…”
Section: Tourism Safetymentioning
confidence: 97%
“…It can also be applied to regression analysis of matrices and examine interaction effects between multiple networks [45]. The method has been shown to be robust and reliable by several scholars [46][47], avoiding issues of multiple collinearities of independent variables in causality analysis.…”
Section: Quadratic Assignment Proceduresmentioning
confidence: 99%